Healthy Eating: CALCIUM - Linda B. Bobroff (EDIS)
Revised! FCS-8561, a 1-page illustrated handout by Linda B. Bobroff, uses a question-and-answer format to provide key information for elders about why calcium is important, what foods contain it, good sources of calcium, and how much older adults need. Published by the UF Department of Family Youth and Consumer Sciences, March 2010.